Analisis Potensi Longsor Rombakan (Debris Flow) dengan Pemodelan Aliran di Lereng Gunung Abang, Kintamani, Bali. - Sinarta, I Nengah; Wahyuni, Putu Ika (Department of Civil Engineering, Diponegoro University, 2022)
Debris flow was mass movement such as; clay, fine sand, organic waste and coarse material such as; gravel, rocks, organic waste, logs mixed with water. Based on historical information the slope of the ancient caldera of Mount Batur that were potentially threatened for the village with debris flows hazards including; Trunyan, Abang Batudinding and Buahan Village. Modeling with DFLOWZ software was supported by spatial data with input parameters namely; Digital Elevation Model (DEM) data and Polyline data. Modeling was an initial approach in predicting the debris inundation area. Research results to get the type of material and debris flow direction. The observed flow anatomy was debris flow in valleys and rivers at an altitude of ± 1500 msl, curved in the valleys of the hills and the direction of flow is to the west. The DFLOWZ analysis shows that the retained deposit area that has the potential to cause debris avalanches is 49,830 m2, with an inundation height based on 5-7 m thick slope valley. The results of the modeling serve as a form of early warning for communities affected by the threat of inundation of debris flows.